Meiosis in bulbous flower species Lycoris: dances underground - Ren, Ziming; Wang, Jingru; Huang, Nan; Fu, Huiqi; Liu, Bing; Xia, Yiping (Frontiers in Plant Science, 2026)
Lycoris, a perennial bulbous flower species, is valued for ornamental features and abundant medicinal ingredients. The reproductive development features of Lycoris, especially meiosis, remain largely uncharacterized, which hinders its breeding programs. However, the references for investigating meiosis in Lycoris are limited at present. In addition, a special reproductive trait of Lycoris that typically differs from other species is that its meiosis occurs in bulbs underground, which increases the difficulties in cytological dissection of sexual cells. In this study, we analyzed meiotic chromosome behaviors in two diploid Lycoris species (L. sprengeri and L. aurea) and two naturally-derived allotriploid varieties (L. chunxiaoensi and L. hubeiensis). The correlation of anther size and the stage of meiosis was determined, which revealed differences between diploid species. Diploid Lycoris showed defects in chromosome segregation, indicating that meiosis in Lycoris is unstable. Meiotic restitution, which defines non-reductional meiosis events, was observed in both diploid species, implying a potential to yield unreduced gametes and thus may explain the natural derivation of polyploids. Immunolocalization of the recombinase HEI10 revealed that L. sprengeri and L. aurea have similar class-I type crossover rates. Moreover, we showed that allotriploid Lycoris exhibit severely disrupted chromosome pairing and bivalent formation, the levels of which varied between varieties. These meiotic defects leaded to aneuploid meiotic products and sterility. Taken together, this study provides a cytological reference and insights into meiosis features in Lycoris, which paves a rode for further studies on reproductive biology and genetics in this special bulbous flower species.